The Angry God in the Mirror Stage: Applications of Lacanian Psychoanalysis to the Naturalization of Violence in Men's Studies in Religion - Green, Kyle (University of Ottawa (Canada), 2010)
In this thesis I discuss some relationships and conversations that occur---and some that could occur in the future---among authors in men's studies in religion and those who work with Jacques Lacan's psychoanalytical model. I focus on how "male violence" is discussed in men's studies in religion. I do this to make projections about why trends in men's studies in religion regarding concepts about violence appear as they do. In the first chapter I attempt to present my theoretical and methodological bias. I locate my interpretation in Judith Butler's theories regarding performance and citation. I then present significant working definitions for the following chapters that remain consistent throughout the thesis. In the second chapter I present a literature review regarding men's studies in religion. I present French feminist ideas about God and masculinity as contributing to motivational ideologies in the field. I then identify mythopoetic and masculinist authors as producing the field's momentum. I lastly present a number of current authors and themes that show a central focus regarding a link between masculinities and violence in the field. In the third chapter I present a literature review about Lacan's psychoanalytic theories regarding the subject and signification. I begin by analyzing Lacan's primary sources in his two most substantial works: Ecrits and The Four Fundamental Concepts of Psycho-Analysis. I then explore how contemporary Lacanian theorists shift his ideas in productive and interesting ways. I lastly show how Lacanian signification can be used to interpret the ways in which authors who contribute to men's studies in religion signify such concepts as "masculinities" and "violence". In the fourth chapter I build upon a Lacanian theoretical model using a Foucauldian framework regarding institutional knowledge. I show how authors in men's studies in religion methodologically and implicitly cite a perceived institutional understanding about violence. Using Jeremy Carrette's focus on the importance of utterances in institutions, I will show that feminist ideologies compose "mechanisms of coercion" for authors who signify violence and masculinity. In the fifth chapter I combine Foucault's work concerning institutional knowledge with Lacan's theories about signification. I show that signification in men's studies in religion is coerced by a feminist re-definition regarding violence. I argue that this re-definition is best defined as Lacanian trauma, and that this trauma is so effective in the field because the traumatic event has to do with re-defining Jewish and Christian conceptions regarding God's masculinity. This thesis has implications for possible ways in which authors in men's studies in religion can approach violence in future work. This thesis composes, or highlights, a conversation between Lacanian psychoanalysis and studies about masculinity. The contribution is thus to two fields because it presents new avenues for discussion that are not yet explored, while drawing on current, relevant and productive work from significant contemporary authors.
Keywords: Religion, General.; Psychology, General.